Women's education in early modern Europe : a history, 1500-1800 - Whitehead, Barbara J. (Garland reference library of social science ;, 1999)
The notion of education as "preparation for one's station in life" is explored in these essays. They look at what constituted education for women in early modern Europe and show the gender-specific nature of teaching